2013
DOI: 10.1080/10934529.2013.781878
|View full text |Cite
|
Sign up to set email alerts
|

Method for toxicity test of titanium dioxide nanoparticles in ciliate protozoanTetrahymena

Abstract: Titanium dioxide (TiO2) nanoparticles have a high surface-to-mass ratio and rapidly aggregate in water causing great difficulties for toxicity test exposed to aquatic organisms or other cell lines. This study uses a cell viability kit for routine toxicity test of TiO2 as well as other nanoparticles which accumulate in the aquatic environment. Tetrahymena immediately endocytoses TiO2 nanoparticles and stores them in food vacuoles until the particles undergo exocytosis as larger aggregates. However, during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, the molecular mechanism of this particle internalization into Tetrahymena was not clear. In addition, the size distribution and zeta-potential of these two nanoparticles were not measured in PPY-medium in this study; size distribution of nanoparticles in PPY-medium was shown in our previous literature [23].…”
Section: Methodsmentioning
confidence: 61%
See 4 more Smart Citations
“…However, the molecular mechanism of this particle internalization into Tetrahymena was not clear. In addition, the size distribution and zeta-potential of these two nanoparticles were not measured in PPY-medium in this study; size distribution of nanoparticles in PPY-medium was shown in our previous literature [23].…”
Section: Methodsmentioning
confidence: 61%
“…Nevertheless, nanoparticle tends to accumulate in the well plates due to the presence of complex PPY medium with the association of many ions. It is also recently reported upon a microscopic study that this accumulation of nanoparticle increases significantly when Tetrahymena species was cultivated in the PPY medium [23]. Tetrahymena cell internalize all free nanoparticles and finally exocytose them as larger aggregates into the culture medium, and this process continues until free small and visible nanoparticles are present the PPY-medium.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations